In the midst of winter [compact disc, unabridged] : a novel - Allende, Isabel (Audioworks, Simon & Schuster Audio, 2017)
A minor traffic accident becomes a catalyst for an unexpected bond among a human rights scholar in Brooklyn, his Chilean tenant, and an undocumented immigrant from Guatemala, who explore the difficulties of immigrants and refugees.